FUTURE CHALLENGES IN THE WAKE OF COVID-19 ON MENTAL HEALTH IN PAKISTAN- A SYSTEMATIC REVIEW - Seemi Tanvir; Mariam Babar; Ayesha Fazal; Faiqa Fazal (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Coronavirus disease (COVID-19) is a contagious disease that has shaken the mankind. Up till 30th June 2020, about 10.1 million people have been affected across 188 countries around the world. Deterioration of mental health is long-term effect of a pandemic. Methods for the control of COVID-19 have provoked fear, anxiety and frustration. Developed countries might be able to handle them but for a developing country it may prove an economic “Death Warrant”. Pakistan is one of countries that have been fighting with COVID-19, with about 24% of the population living below the national poverty line and aftermaths of this pandemic still awaits. We intend to assess impact of COVID-19 on mental health in Pakistan to contribute towards the prevention of anticipated complications by getting a more clear picture.METHODOLOGY: Online literature search was carried out from Jan 2020 to Jun 2020, using Google Scholar, Science Direct and PubMed with the help of key words. This resulted in retrieval of 151 articles after removing duplicated ones. Articles with incomplete information, case reports, case series, letters or editorials were also excluded. After shortlisting, seven articles were finally selected for the review.RESULTS: This review observed that mental illnesses have been potentiated by COVID-19 due to its multi-dimensional manifestations especially on the economic growth of the country. Health care professionals and those having previous history of any psychological disabilities are the easy targets.CONCLUSION: COVID-19 disease management and preventive measures to provide psychological support must go hand in hand.